Synthesis of the transforming mechanism of the rocking machine (Journal of Mathematics Mechanics and Computer Science, 2022)
This article discusses the synthesis of a six-link transforming mechanism of a rocking machine.First, the problem of synthesizing a four-link articulated-lever mechanism for reproducing a verticalline was solved. For this purpose, the problem of synthesizing a rectilinear-guiding mechanism ofthe Evans type, which is a hinged-lever four-link mechanism with a straight vertical line drawingpoint, is considered. The task of synthesis is to implement the constraint equation. The geometricmeaning of the constraint equation is to determine the hinge, the positions of which in the absolutecoordinate system are equidistant from the origin of the OXY coordinate system.The problem of synthesis is formulated as a problem of quadratic approximation. According to thefound dimensions of the articulated four-link, performing the position analysis, the true positionsof the suspension point of the rod column were determined. After that, the found parameterswere refined using the output criterion directly, that is, the deviation from the given rectilineartrajectory.After the synthesis of a straight-line guiding mechanism, a drive kinematic chain was synthesized,which consists of a crank and a connecting rod.Thus, a rocking machine drive mechanism was obtained, containing a base, a crank pair connectedto the main hinged four-link mechanism. The technical result is achieved by the fact that a two-linkgroup is attached to the main four-link mechanism, forming a class III mechanism. The attachedtwo-drive group is the leading crank connected to the rack and connecting rod.Based on the obtained dimensions of the six-link converting mechanism, an experimental modelwas developed, which fully confirmed the efficiency of the transforming mechanism.
Keywords: Synthesis; rocking machine; drive; connecting rod; four-link articulated-lever mechanism; converting mechanism